(3GdQSGdI GdjJjeI aj BOGH Gdedhcs - (3YHO Gddg Hf GdebaY , GHf GdebaY , CHh YeQ,J (B142 (3g` s ((3eMeO Hf Ydi Hf YejQI GdeQjfi GdeGdci s)
(3ChdgG (B:s
(3bGd YHO Gddg Hf GdebaY (B: (3hLOfG GdfGS bHdfG cGfhG ge CYXe CLSGOkG hCYXe eY CLSGOge CMdGeG s
(3BNQgG (B:s
(3hGJNPge ENhGfkG hdG JJNPge CYOGA , hdG JfGaSge ai GdcdeI jJbQHhf HgG Ch GdYde jDeQhf Hg Ef TGA Gddg cedJ GdQSGdI GdjJjeI s
(3HgG fXGe GdJYbjHIs
(3cJH JGQjN GdfSN HGdbde GdaGSi hgj QShe hCTcGd jUYH JRhjQgG Ch eMGcGJgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B156s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B- (3GdQHGW (B(328 (3b (B/ 3) s
Keywords: (3GdSjGSI hGdGLJeGYs